Progressive Functional and Neuroretinal Affectation in Patients With Multiple Sclerosis Treated With Fingolimod. Issue 4 (December 2021) - Garcia-Martin, Elena; Ruiz de Gopegui, Erika; Satue, Maria; Gil-Arribas, Laura; Jarauta, Laura; Ara, Jose R.; Martin, Jesus; Fernandez, Francisco J.; Vilades, Elisa; Rodrigo, Maria J.
Abstract : Background: To evaluate the effect of fingolimod in visual function and neuroretinal structures in patients with multiple sclerosis (MS) for a period of 1 year. Methods: This longitudinal and observational cohort study included 78 eyes of 78 patients with MS treated with fingolimod. All subjects were evaluated every 3 months during 12 months and compared with 32 patients treated with interferon beta. All patients were examined for high-contrast and low-contrast (2.5% and 1.25%) visual acuity (VA), contrast sensitivity vision (CSV) (using Pelli–Robson and CSV-1000E tests), color vision (Farnsworth D-15 and L'Anthony D-15 desaturated tests), and retinal structural measurements (retinal nerve fiber layer [RNFL] and ganglion cell layer [GCL] thickness) using optical coherence tomography (OCT) technology. Results: Patients with MS treated with fingolimod for a period of 1 year showed significant reduction in 100% and 1.25% contrast VA ( P = 0.009 and 0.008, respectively), an alteration of contrast sensitivity and color perception (Pelli–Robson test, CSV-1000E test, Farnsworth D-15 desaturated test, and L'Anthony D-15 desaturated test; P < 0.001), GCL thickness reduction ( P = 0.007), and an average macular central thickness increase of 2.6 μm ( P = 0.006). Patients with MS treated with interferon beta did not show significant changes in visual function tests neither in macular thickness measurements, but they showed a significant reduction in GCL and RNFL thicknesses. The reduction in neuroretinal structures observed by OCT was significantly higher in the interferon-beta group, but patients treated with fingolimod showed a significant increase in macular central thickness and a reduction in low contrast vision ( P < 0.001). Conclusions: Patients with MS treated with fingolimod and with no clinically observable macular edema show a significant change in visual function parameters and average macular central thickness increase compared with those treated with interferon beta. These findings are probably due to subclinical macular edema produced by fingolimod, which might be considered as an indicator for pharmacovigilance of sphingosine-1-phosphate inhibitors to be improved.